COMBINING ABILITY AND HETEROSIS ANALYSIS FOR GRAIN YIELD TRAITS IN FINE LONG GRAIN RICE (ORYZA SATIVA L.) - A. Rasheed; M. Ashfaq; M. Sajjad (Journal of Animal and Plant Sciences, 2020)
Experiment was conducted to study combining ability and heterosis for major yield traits namely days to 50% flowering (DF50), growth duration (GD), plant height (PH), effective panicles per plant (EP/Pl), panicle length (PL), grains per panicle (G/P), filled grains/panicle (FG/P), seed setting rate (SSR), 1000-grains weight (TGW), grain yield/plot ( GY/plot), grain yield/hectare (GY/ha). From Griffing’s analysis maximum general combining ability was found in L-203, CB-15 and CB-42 for PL, SSR, PH and G/P. The maximum specific combining ability was found in L-203 × CB-42 for PH, L-203 × Jasmine-85 for G/P, FG/P and CB-15 × CB-40 for GY/ha. The results revealed that for hybrid breeding, maximum heterosis could be exploited in crosses ‘Jasmine-85 × CB-42’, ‘CB-15 × CB-42’ and ‘Jasmine-85 × CB-15’ for major yield related traits. Taken together the results suggested potential use of the parents/crosses used herein for breeding commercial hybrid rice varieties as well as for the enhancement of the germplasm resources.
Keywords: Rice; Combining Ability; Heterosis; Traits; Diallel; Hybridization